La prise en compte du statut d'époux par le droit des affaires de l'Organisation pour l'Harmonisation en Afrique du Droit des Affaires (OHADA) - André Desmonds Eyango Djombi (Juridical Tribune, 2015)
Taking into account the status of spouses by business law of the Organization for the Harmonization of African Business Law (OHADA) is referring to general commercial law and company law. The OHADA legislator values the status of spouses devoting equality between spouses, through the possibility for them to be able to be involved in low risk companies; the recognition of the de facto company between them and the right granted to each power, under the same conditions, benefit from the commercial lease originally attached to privileges. The consideration that the OHADA law grants the quality of husband appears in heritage protection thereof, insofar as it puts it away in case of depletion bad deal made by one of them . This is why the prohibition for spouses to be involved in the unlimited risk firms and the requirement of a separate trade as a condition for the spouse of the trader can also acquire the same status. But the heritage protection system spouse taken from the OHADA business law is supplemented by certain mechanisms of civil law, including matrimonial property regimes, although not all have the same efficiency. Indeed, among the two groups of matrimonial property regimes are known as separation schemes and those of the community property, only the first effectively protect the couple's assets. This objective likely was not assigned to the second from the design. These look more forward the merger of most of the assets of the couple without the slightest idea of calculation.